A method for detecting coverage of a single layer of a two-dimensional material of a poor electrical conductor

CN117705879BActive Publication Date: 2026-10-27ZHENGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311691232.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2026-10-27
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

[0005]为了解决上述现有技术中针对目前二维纳米材料薄膜大面积范围检测的难题,本发明提供一种检测不良电导体二维材料单层薄膜覆盖度的方法

Benefits of technology

[0023]本发明通过将待测二维材料沉积于导电基底A上,形成表面沉积有二维材料单层薄膜的待测基底;再在所述待测基底上平行覆盖一个导电基底B,使导电基底B与所述二维材料单层薄膜相接触,封装以形成由上至下依次为导电基底B、二维材料单层薄膜、导电基底A的三明治结构的待测结构。本发明的构思基于该待测结构的工作原理,当该待测结构受到压力时,待测结构中的导电基底B发生变形从而穿过不连续的二维材料单层薄膜与导电基底A发生接触,从而产生电流的响应。并且具有该结构的待测结构导电基底B与导电基底A之间的接触面积会随着压力的增加而增加,待测结构产生的电流响应也会随之增加,直至导电基底B在压力的作用下穿过不连续的二维材料单层薄膜与导电基底A之间的接触面积达到饱和,故待测结构的理论等效电路是由两个导电基底的电阻和两导电基底之间接触电阻串联而成,由于二维材料本身是不良导体,待测结构接触电阻远大于两个导电基底本身电阻,待测结构随压力的增加而产生的电流响应主要由接触电阻变化引起,故待测结构的总电阻近似为接触电阻,进而能够通过测试上述待测结构的压力-电流响应曲线,通过结合理论模型公式对其拟合,以获得最终薄膜覆盖度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117705879B_ABST
    Figure CN117705879B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of nanomaterial detection, and discloses a method for detecting coverage of a single-layer film of a two-dimensional material of a poor conductor, comprising the following steps: depositing the two-dimensional material to be detected on a conductive substrate A to form a test substrate with a single-layer film of the two-dimensional material deposited on the surface; covering the test substrate with a conductive substrate B in parallel to form a sandwich structure; under certain voltage conditions, uniformly applying pressure to the test structure at a constant compression rate to obtain a pressure-current response curve; fitting the obtained pressure-current response data using a theoretical model formula to obtain the coverage area of the single-layer film of the two-dimensional material; testing the fitting result, and selecting the coverage rate of the fitting degree R 2 >0.98000 as the final film coverage. The detection method can detect the coverage of the single-layer film of the two-dimensional material in a large area range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanomaterial detection technology, and in particular to a method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity. Background Technology

[0002] Compared to macroscopic materials, nanomaterials exhibit unique properties in terms of force, electricity, magnetism, and heat due to surface and interface effects, small size effects, and macroscopic quantum tunneling effects. Two-dimensional nanomaterials, with their unique two-dimensional structure, good crystal integrity, high mechanical flexibility, large specific surface area, and excellent electrical conductivity, have become popular materials in many fields such as sensing, batteries, and medicine.

[0003] Two-dimensional nanomaterials can be deposited on substrate surfaces using nanotechnology (e.g., Langmuir-Blodgett deposition, spin coating, self-assembly, or electrophoresis). The deposition pattern can be controlled by manipulating process parameters. These nanofilms offer significant advantages in crystal film growth and the fabrication of electronic test structures. However, achieving the desired coverage of the resulting two-dimensional nanomaterial films is difficult, limiting their practical applications. Current detection methods for nanomaterials are also quite limited. Atomic force microscopy (AFM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) can only detect small areas. Furthermore, SEM bombards the sample surface with incident electrons, potentially damaging the material. Therefore, a non-destructive method is urgently needed to assess the coverage of two-dimensional nanomaterial films over a large area.

[0004] Therefore, the present invention provides a method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity. Summary of the Invention

[0005] To address the challenges of large-area detection of two-dimensional nanomaterial thin films in existing technologies, this invention provides a method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity. This invention involves depositing the two-dimensional material to be tested, which has poor electrical conductivity, onto a good conductive substrate to form a substrate with a single-layer thin film of the two-dimensional material deposited on its surface. Then, a conductive substrate is placed parallel to the substrate to be tested, bringing the conductive substrate into contact with the single-layer thin film of the two-dimensional material. This encapsulation forms a sandwich structure of the test structure, where the theoretical equivalent circuit of the test structure consists of the resistances of the two conductive substrates and the contact resistance between them connected in series. Since the two-dimensional material itself is a poor conductor, the contact resistance of the test structure is much greater than the resistance of the two conductive substrates themselves. The current response of the test structure to increase pressure is mainly caused by the change in contact resistance. Therefore, the total resistance of the test structure is approximately equal to the contact resistance. Thus, by testing the pressure-current response curve of the test structure and fitting it with a theoretical model formula, the final film coverage can be obtained.

[0006] The present invention provides a method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity, achieved through the following technical solution:

[0007] A method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity includes the following steps:

[0008] The two-dimensional material to be tested is deposited on a conductive substrate A to form a substrate to be tested with a two-dimensional material monolayer film deposited on its surface; then, a conductive substrate B is placed parallel to the substrate to be tested, so that the conductive substrate B and the two-dimensional material monolayer film are in contact, and encapsulation is performed to form a sandwich structure of conductive substrate B, two-dimensional material monolayer film and conductive substrate A from top to bottom, thus obtaining the structure to be tested.

[0009] Wherein, the conductive substrate A is a good conductive substrate;

[0010] Under the condition of applied voltage, pressure is uniformly applied to the structure under test at a constant compression rate, and the change of current of the structure under test with the applied pressure is recorded to obtain pressure-current response data.

[0011] The pressure-current response data were fitted using theoretical model formulas to obtain the pressure-current response curve of the two-dimensional material monolayer thin film, with a goodness of fit R. 2 >0.98000; A obtained from the fitting results max The ratio of the overlapping area between the two-dimensional material monolayer film and the conductive substrate B is used as the film coverage:

[0012] The theoretical model formula is as follows:

[0013] Among them, A max denoted as ρ, where ρ is the maximum contact area between two conductive substrates through a single layer of two-dimensional material, r is a parameter reflecting sensitivity, P0 is the pressure threshold, U is the voltage, ρ is the contact resistance resistivity, and I is the response current of the structure under test.

[0014] Preferably, the encapsulation process uses polyimide tape for encapsulation.

[0015] Preferably, the two-dimensional material single-layer film is a poor electrical conductor.

[0016] Preferably, the two-dimensional material monolayer film is a discontinuous semiconductor or a discontinuous insulating material.

[0017] Preferably, the good conductive substrate is any one of Ni / Si and ITO / PET.

[0018] Preferably, the conductive substrate B is a flexible substrate.

[0019] Preferably, the flexible substrate is ITO / PET.

[0020] Preferably, the applied voltage during the test is 0.5 to 1.5V.

[0021] Preferably, pressure is applied uniformly to the structure to be tested, and the compression rate is 5 to 25 mm / min.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] This invention involves depositing the two-dimensional material to be tested onto a conductive substrate A to form a substrate with a single-layer thin film of the two-dimensional material deposited on its surface. A conductive substrate B is then placed parallel to the substrate under test, bringing the conductive substrate B into contact with the single-layer thin film of the two-dimensional material. This encapsulation forms a sandwich structure of test structure, consisting of conductive substrate B, the single-layer thin film of the two-dimensional material, and conductive substrate A, from top to bottom. The concept of this invention is based on the working principle of this test structure. When the test structure is subjected to pressure, the conductive substrate B deforms, allowing it to penetrate the discontinuous single-layer thin film of the two-dimensional material and make contact with the conductive substrate A, thereby generating a current response. Furthermore, the contact area between the conductive substrate B and the conductive substrate A of the test structure with this structure increases with increasing pressure, and the current response generated by the test structure also increases accordingly, until the contact area between the conductive substrate B and the conductive substrate A reaches saturation under pressure, through the discontinuous two-dimensional material monolayer film. Therefore, the theoretical equivalent circuit of the test structure is composed of the resistance of the two conductive substrates and the contact resistance between the two conductive substrates in series. Since the two-dimensional material itself is a poor conductor, the contact resistance of the test structure is much greater than the resistance of the two conductive substrates themselves. The current response generated by the test structure with increasing pressure is mainly caused by the change in contact resistance. Therefore, the total resistance of the test structure is approximately equal to the contact resistance. Thus, by testing the pressure-current response curve of the test structure and fitting it with the theoretical model formula, the final film coverage can be obtained.

[0024] The detection method of this invention can detect the coverage of a two-dimensional material monolayer film by fitting the pressure-current data of the structure under test through a theoretical model formula. Moreover, the detection method of this invention can detect the coverage of a two-dimensional material monolayer film over a large area (centimeter level), which is a significant advantage compared to the detection range (micrometer level) of existing detection methods. Furthermore, the detection process does not damage the two-dimensional material monolayer film and will not affect the further application of the film. In addition, the testing process is simple, low-cost, and has no complicated testing steps, making it easy to operate and highly accurate. Attached Figure Description

[0025] Figure 1 This is a structural diagram of the structure to be tested in this invention.

[0026] Figure 2 A location map for AFM detection of a conductive substrate with two-dimensional nanofilm deposition;

[0027] Figure 3 This is a fitting graph of the pressure-current response data of the structure under test using the mathematical model formula in Example 1;

[0028] Figure 4 This is an atomic force electron microscope image of the coverage of the two-dimensional nanofilm in five regions in Example 1;

[0029] Figure 5 This is an atomic force electron microscope image of the coverage of the two-dimensional nanofilm in five regions in Example 2;

[0030] Figure 6 This is a fitting graph of the pressure-current response data of the structure under test using the mathematical model formula in Example 2;

[0031] Figure 7 This is an atomic force electron microscope image of the coverage of the two-dimensional nanofilm in five regions in Example 3;

[0032] Figure 8 This is a fitting graph of the pressure-current response data of the structure under test using the mathematical model formula in Example 3.

[0033] Figure 9 This is an atomic force electron microscope image of the coverage of the two-dimensional nanofilm in five regions in Example 4;

[0034] Figure 10 This is a fitting graph of the pressure-current response data of the structure under test using the mathematical model formula in Example 4. Detailed Implementation

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below.

[0036] This invention provides a method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity, comprising the following steps:

[0037] Step 1, Prepare the structure to be tested:

[0038] The two-dimensional material to be tested is deposited on a conductive substrate A to form a substrate with a two-dimensional material monolayer film deposited on its surface. Subsequently, a conductive substrate B is placed parallel to the substrate to be tested, so that the conductive substrate B and the two-dimensional material monolayer film are in contact. The substrate is then encapsulated to form a sandwich structure consisting of conductive substrate B, two-dimensional material monolayer film, and conductive substrate A from top to bottom, thus obtaining the structure to be tested.

[0039] Wherein, the conductive substrate A is a good conductive substrate;

[0040] Step 2: Test the structure under test and obtain pressure-current response data:

[0041] Under the condition of applied voltage, pressure is uniformly applied to the structure under test at a constant compression rate, and the change of current of the structure under test with the applied pressure is recorded to obtain pressure-current response data.

[0042] Step 3: Fit the pressure-current response curve to obtain the film coverage.

[0043] The pressure-current response data were fitted using theoretical model formulas to obtain the pressure-current response curve of the two-dimensional material monolayer thin film, with a goodness of fit R. 2 >0.98000; A obtained from the fitting results max The ratio of the overlapping area between the two-dimensional material monolayer film and the conductive substrate B is used as the film coverage:

[0044] The theoretical model formula is as follows:

[0045] Among them, A max denoted as ρ, where ρ is the maximum contact area between two conductive substrates through a single layer of two-dimensional material, r is a parameter reflecting sensitivity, P0 is the pressure threshold, U is the voltage, ρ is the contact resistance resistivity, and I is the response current of the structure under test.

[0046] It should be noted that the use of poor conductor films such as two-dimensional oxides is generally on electrode materials, i.e., conductive materials. Therefore, this invention is a method for detecting the coverage of two-dimensional materials (discontinuous semiconductors or discontinuous insulating materials) developed with consideration of the application scenarios of poor conductor two-dimensional thin films. Specifically, it involves depositing the material onto a conductive substrate A, which serves as a good conductive substrate. During the deposition process, the selected deposition process is the same as that used in the actual application of the two-dimensional material monolayer film with the poor conductor. This ensures that the coverage of the tested two-dimensional material monolayer film is consistent with the coverage of the actual applied two-dimensional material monolayer film. Because the detection method does not damage the two-dimensional material, after detecting the coverage of the two-dimensional material monolayer film, the tested structure can be disassembled, and the good conductive substrate covered with the two-dimensional material can be removed for practical application, thus ensuring that the detected coverage of the two-dimensional material monolayer film is consistent with the coverage of the actual applied two-dimensional material monolayer film. Furthermore, to better illustrate the effectiveness of this method, in a preferred embodiment of the invention, either Ni / Si or ITO / PET is used as a good conductive substrate. ITO / PET is chosen as a good conductive substrate because it is a commonly used flexible transparent substrate that is prone to deformation under pressure. Ni / Si is chosen as a good conductive substrate because silicon-based structures under test are the most commonly used substrate material in the microelectronics industry. The Si substrate was purchased from Shun Sheng Electronics Technology (4-inch 100mm single-polished silicon wafer), and the Ni electrode was deposited on the Si substrate using magnetron sputtering. The ITO / PET substrate was purchased from Regruis.

[0047] During the assembly of the structure under test (DUT), a conductive substrate B is used so that when the DUT is subjected to pressure, the conductive substrate B can deform, thereby passing through the gaps in the discontinuous two-dimensional material monolayer film and making contact with the conductive substrate A, thus generating current. In a preferred embodiment of the present invention, a flexible conductive substrate, such as an ITO / PET substrate, is used as the conductive substrate B. After the conductive substrate B is covered onto the two-dimensional material monolayer film on the DUT, polyimide tape is used as the encapsulation material for encapsulation, thereby obtaining the DUT. Then, conductive silver paste is used to connect the upper and lower conductive substrates of the DUT to copper wires. The use of polyimide tape as an encapsulation material for encapsulating the electronic DUT is a conventional method in the art, so the specific encapsulation steps are not described in detail here.

[0048] During the testing of the structure under test, a Mark-10 universal testing machine and a Keithley 2450 current source meter were used. The specific testing method was as follows: the structure under test was connected to the Keithley 2450 current source meter via copper wire to detect the current in the structure. The structure under test was then placed on the Mark-10 universal testing machine to apply pressure. As the universal testing machine continuously applied pressure to the structure under test, the current response of the structure was collected by the Keithley 2450 current source meter. The voltage of the current source meter was set to 1V during the test. The pressure change applied to the structure under test could be obtained from the universal testing machine, and the compression rate of the structure under test could also be set through the testing machine.

[0049] During the testing of the aforementioned structure under test, the voltage and compression rate can be adjusted according to the actual structure under test. The instrument is not limited to the models mentioned above, as long as it ensures stable operation of the structure under test at the selected voltage and compression rate. For example, the selected voltage can be 0.5–1.5V, and the compression rate can be 5–25 mm / min.

[0050] Example 1

[0051] This embodiment provides a method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity, including the following steps:

[0052] Step 1: Deposit a two-dimensional material monolayer thin film on a conductive substrate A

[0053] In this embodiment, a Ni / Si good conductive substrate is used as the conductive substrate A, and two-dimensional calcium niobate is used as a two-dimensional material, which is deposited on the conductive substrate A.

[0054] Step 2, prepare the structure to be tested:

[0055] The structure to be tested in this embodiment is as follows: Figure 1As shown, a conductive substrate (Ni / Si) covered with a two-dimensional material (two-dimensional calcium niobate) film and a blank flexible conductive substrate (ITO / PET) are overlapped face-to-face, with an overlap area of ​​1×1 cm. 2 It is assembled by bonding with polyimide tape. For the specific preparation steps of the structure to be tested, please refer to patent CN111366275A.

[0056] Step 3: Test the structure under test and plot the pressure-current response curve:

[0057] The specific testing method involves connecting the structure under test (SUT) to a Keithley 2450 current source meter via copper wire, placing the SUT on the sample stage of a universal testing machine, applying a 1V voltage to the SUT using the current source meter, and setting the compression rate of the universal testing machine to 20.00000mm / min. The testing machine then applies uniform pressure to the SUT and continuously records the applied pressure value. The current source meter collects the current response of the SUT during the compression process, thus obtaining the pressure-current response data. The obtained pressure-current response data is then fitted using a theoretical model formula to derive the pressure-current response curve of the two-dimensional monolayer thin film. The goodness of fit R0 is [not specified]. 2 >0.98000; A obtained from the fitting results max The ratio of the overlapping area between the two-dimensional material monolayer film and the conductive substrate B is used as the film coverage:

[0058] The theoretical model formula is as follows:

[0059] Among them, A max The maximum contact area between two conductive substrates through a single layer of two-dimensional material film is given by: r is a parameter reflecting sensitivity, P0 is the pressure threshold, U is the voltage, ρ is the contact resistivity, and I is the response current of the structure under test. In this embodiment, the contact resistivity ρ is determined by the overlap of two conductive substrates without two-dimensional material coverage (overlap area: 1 × 1 cm). 2 The test structure is assembled from polyimide tape, and its maximum current response is calculated from the test structure. Where A... max The two parameters, r and p, are obtained by fitting the formula. P0 is the pressure threshold that causes the current response of the structure under test, the voltage U is 1V, and I and P are obtained from the pressure-current response curve. The final fitting result is as follows: Figure 4 As shown, the fit R 2 =0.99723, A obtained from the fitting results max It is 0.11036cm 2 The coverage rate was 88.964%.

[0060] This invention also employs AFM testing to test the coverage of the two-dimensional calcium niobate in this embodiment, according to multi-region testing (test areas such as...). Figure 2 (As shown) and the coverage is obtained by averaging. The AFM test results are as follows. Figure 4 , Figure 4 a- Figure 4 e corresponds to Figure 2 The AFM plots at the ae position show that the coverage of the two-dimensional nanosheet film in the five regions is 90.260%, 92.400%, 88.260%, 90.610%, and 88.930%, respectively, and the average coverage of the two-dimensional niobate film is 90.092%.

[0061] Figure 4 middle, Figure 4 f- Figure 4 Figure j shows the test pattern of AFM. The area of ​​the two-dimensional material not covered on the Ni / Si substrate was calculated by ImageJ software. The blue area in the figure represents the area of ​​the nanosheet not covered in the test position (ae).

[0062] By comparing the test results of this invention with the results obtained by AFM testing, it can be seen that the difference between the two is only 1.128%. The nanosheet coverage obtained by fitting the theoretical model is very close to the actual coverage of the nanosheet on the Ni / Si substrate, and the fitting result is accurate.

[0063] Example 2

[0064] The structure to be tested in this embodiment is as follows: Figure 1 As shown, the coverage of the two-dimensional material differs from that in Example 1. A conductive substrate (Ni / Si) covered with a two-dimensional material (two-dimensional calcium niobate) film and a blank flexible conductive substrate (ITO / PET) are overlapped face-to-face, with an overlap area of ​​1×1 cm. 2 The structure was assembled using polyimide tape, and the test structure was prepared according to the method described in Chinese patent CN111366275A. The coverage of the two-dimensional calcium niobate film was tested in the same manner as in Example 1, and the AFM test results for the five regions are as follows: Figure 5 As shown, Figure 5 ae correspond to each other in sequence Figure 2 AFM plots of the substrate at positions 1-5. The blue areas in the plot represent the areas not covered by the nanosheets at the test positions (ae). The coverage of the two-dimensional calcium niobate film at these positions is 62.620%, 43.800%, 77.560%, 78.920%, and 82.080%, respectively, with an average coverage of 68.996%.

[0065] Figure 5 middle, Figure 5 f- Figure 5Figure j shows the test pattern of AFM. The area of ​​the two-dimensional material not covered on the Ni / Si substrate was calculated by ImageJ software. The blue area in the figure represents the area of ​​the nanosheet not covered in the test position (ae).

[0066] The method of the present invention is tested according to the following parts:

[0067] 1) Connect the structure under test to the Keithley 2450 current source meter via copper wire, and place the structure under test on the sample stage of the universal testing machine. Apply a voltage of 1V to the structure under test with the current source meter. Set the compression rate of the universal testing machine to 20mm / min. Then, the testing machine applies pressure to the structure under test uniformly. The testing machine will continuously record the pressure value applied to the structure under test, and the current source meter will collect the current response of the structure under test during the compression process, thereby obtaining the pressure-current response data of the structure under test.

[0068] 2) The contact resistivity ρ is determined by the overlap of two conductive substrates without two-dimensional material covering them (overlapping area: 1×1cm). 2 The test structure is assembled from polyimide tape and the maximum current response of the test structure is calculated.

[0069] 3) The obtained pressure-current response data are fitted using the theoretical model formula proposed in this invention, where A max The two parameters, r and p, are obtained by fitting the formula. P0 is the pressure threshold that generates a current response from the structure under test, and the voltage U is 1V. I and P are obtained from the pressure-current response curve. The fitting results are as follows: Figure 6 As shown, the fit R 2 =0.99761, A obtained from the fitting results max The value is 0.32054, and the coverage of the two-dimensional material single-layer film is 67.946%.

[0070] Comparing the results with those obtained from AFM testing, the difference is 1.050%. The nanosheet coverage obtained by fitting the theoretical model is very close to the actual coverage of the nanosheets on the Ni / Si substrate, indicating that the fitting result is accurate.

[0071] Example 3

[0072] The required structure to be tested in this embodiment is as follows: Figure 1 As shown, the coverage of the two-dimensional material differs from the above embodiment. A conductive substrate (Ni / Si) covered with a two-dimensional material (two-dimensional calcium niobate) film and a blank flexible conductive substrate (ITO / PET) are overlapped face-to-face, with an overlap area of ​​1×1 cm. 2The structure was assembled using polyimide tape. For specific preparation steps of the structure under test, please refer to the authorized patent CN111366275A. The coverage of the two-dimensional calcium niobate film was tested in the same manner as in Example 1. The AFM test results for the five regions are as follows: Figure 7 As shown, Figure 7 a- Figure 7 e corresponds to Figure 2 The AFM images of positions 1-5 on the substrate show that the coverage of the two-dimensional calcium niobate film is 70.790%, 80.030%, 80.630%, 84.710%, and 85.430%, respectively, with an average coverage of 80.318%.

[0073] Figure 7 middle, Figure 7 f- Figure 7 Figure j shows the test pattern of AFM. The area of ​​the two-dimensional material not covered on the Ni / Si substrate was calculated by ImageJ software. The blue area in the figure represents the area of ​​the nanosheet not covered in the test position (ae).

[0074] The method of the present invention is tested according to the following parts:

[0075] 1) Connect the structure under test to the Keithley 2450 current source meter via copper wire, and place the structure under test on the sample stage of the universal testing machine. Apply a voltage of 1V to the structure under test with the current source meter. Set the compression rate of the universal testing machine to 20mm / min. Then, the testing machine applies pressure to the structure under test uniformly. The testing machine will continuously record the pressure value applied to the structure under test, and the current source meter will collect the current response of the structure under test during the compression process, thereby obtaining the pressure-current response data of the structure under test.

[0076] 2) The contact resistivity ρ is determined by the overlap of two conductive substrates without two-dimensional material covering them (overlapping area: 1×1cm). 2 The test structure is assembled from polyimide tape and the maximum current response of the test structure is calculated.

[0077] 3) The obtained pressure-current response data are fitted using the theoretical model formula proposed in this invention, where A max The two parameters, r and p, are obtained by fitting the formula. P0 is the pressure threshold at which the structure under test generates a current response, and the voltage U is 1V. I and P are obtained from the current-pressure curve. The fitting result is as follows: Figure 8 As shown, the fit R 2 =0.98723, A obtained from the fitting results max It is 0.16991cm 2 The coverage of the two-dimensional material single-layer film is 83.009%.

[0078] Comparing the results with those obtained from AFM testing, the difference is 2.691%. The nanosheet coverage obtained by fitting the theoretical model is very close to the actual coverage of the nanosheets on the Ni / Si substrate, indicating that the fitting result is accurate.

[0079] Example 4

[0080] The required structure to be tested in this embodiment is as follows: Figure 1 As shown, compared to the above embodiments, the two-dimensional material deposited on the Ni / Si substrate in this embodiment is a two-dimensional titanate material. A conductive substrate (Ni / Si) covered with a two-dimensional material (two-dimensional titanate) film and a blank flexible conductive substrate (ITO / PET) are overlapped face-to-face, with an overlap area of ​​1×1 cm. 2 The structure was assembled using polyimide tape. For specific preparation steps of the structure under test, please refer to Chinese authorized patent CN111366275A. The coverage of the two-dimensional titanate film was tested in the same manner as in Example 1. The AFM test results for the five regions are as follows: Figure 9 As shown, Figure 9 a- Figure 9 e corresponds to Figure 2 The AFM images of positions 1-5 on the substrate show that the coverage of the two-dimensional titanate film is 18.170%, 13.670%, 9.140%, 2.760%, and 21.120%, respectively, with an average coverage of 12.972%.

[0081] Figure 9 middle, Figure 9 f- Figure 9 j is the test pattern of AFM, which is calculated by ImageJ software to show the area of ​​the two-dimensional material not covered on the Ni / Si substrate. The blue area in the figure represents the area of ​​the nanosheet not covered at the test position (ae).

[0082] The method of the present invention is tested according to the following parts:

[0083] 1) Connect the structure under test to the Keithley 2450 current source meter via copper wire, and place the structure under test on the sample stage of the universal testing machine. Apply a voltage of 1V to the structure under test with the current source meter. Set the compression rate of the universal testing machine to 20mm / min. Then, the testing machine applies pressure to the structure under test uniformly. The testing machine will continuously record the pressure value applied to the structure under test, and the current source meter will collect the current response of the structure under test during the compression process, thereby obtaining the pressure-current response data of the structure under test.

[0084] 2) The contact resistivity ρ is determined by the overlap of two conductive substrates without two-dimensional material covering them (overlapping area: 1×1cm). 2 The test structure is assembled from polyimide tape and the maximum current response of the test structure is calculated.

[0085] 3) The obtained pressure-current response data are fitted using the theoretical model formula proposed in this invention, where A max The two parameters, r and p, are obtained by fitting the formula. P0 is the pressure threshold at which the structure under test generates a current response, and the voltage U is 1V. I and P are obtained from the current-pressure curve. The fitting result is as follows: Figure 10 As shown, the fit R 2 =0.99777, A obtained from the fitting results max It is 0.87647cm 2 The coverage of the two-dimensional material single-layer film is 12.353%.

[0086] Comparing the results with those obtained from AFM testing, the difference is 0.619%. The nanosheet coverage obtained by fitting the theoretical model is very close to the actual coverage of the nanosheets on the Ni / Si substrate, indicating that the fitting result is accurate.

[0087] It should be noted that, in the above embodiments of the present invention, the two-dimensional calcium niobate used is deposited on the corresponding substrate through the following steps:

[0088] 1) Preparation of Ca2Nb3O 10 - Nanosheet suspension: 0.1–0.8 g K₂CO₃, 1.0–51.9 g CaCO₃, and 2.5–3.8 g Nb₂O₅ were ground and mixed in an agate mortar for 3 hours. The mixture was then placed in an alumina crucible and calcined at 800°C for 1 hour. After natural cooling, the mixture was ground into powder. The powder was then placed back into an alumina crucible and calcined at 1200°C for 12 hours. After natural cooling, the mixture was ground into powder to obtain the precursor potassium calcium niobate (KCa₂Nb₃O₅). 10 It is abbreviated as precursor KCNO;

[0089] 2) Preparation of protonated product HCa2Nb3O 10 3g of the precursor KCNO was placed in 300mL of 2mol / L hydrochloric acid solution and stirred on a magnetic stirrer for 3 days. The hydrochloric acid solution was replaced daily with fresh 2mol / L hydrochloric acid solution. Then, the acid-treated lithium potassium titanate was washed with deionized water by vacuum filtration until the supernatant was neutral. The supernatant was then dried naturally at room temperature to obtain the protonated product HCa2Nb3O. 10 HCNO (abbreviated as HCNO)

[0090] 3) Preparation of CNO nanosheet suspension: Take 0.1g of HCNO powder and 0.238mL of 40% tetrabutylammonium hydroxide solution into a beaker, add water to 20mL, and stir on a magnetic stirrer for 3h to obtain the CNO nanosheet suspension.

[0091] 4) The Langmuir-Blodgett (LB) coating deposition method is as follows:

[0092] Preparation of the conductive substrate: A rectangular conductive substrate, cut to 1.5cm x 1cm, is ultrasonically cleaned in deionized water for 3 minutes; then, it is ultrasonically cleaned in anhydrous ethanol for 3 minutes. The conductive substrate is then removed and its surface is wiped clean with lens paper.

[0093] LB film preparation: Take 2 mL of CNO nanosheet suspension stirred for 3-12 h and put it into a 500 mL beaker. Dilute with water to 500 mL and let stand for 15 min. Then, use a syringe to draw the middle and upper part of the solution and inject it into the LB tank. Rinse the platinum hanging sheet with anhydrous ethanol and ignite it at high temperature. After cooling, place it at an appropriate height in the LB film stretching machine. Clamp the cleaned conductive substrate on the fixture and immerse the conductive substrate in the solution. Be careful not to let the fixture come into contact with the solution.

[0094] LB film stretching: The film stretching speed was set to 0.01–0.50 mm / s and the barrier speed was set to 0.01–0.50 mm / s. Film stretching was performed at 20%, 40%, 60%, 80%, and 100% of the maximum surface pressure, respectively, and niobium oxide nanosheet films were finally obtained.

[0095] Obviously, the above embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A method for detecting the coverage of a single-layer thin film of a two-dimensional material with poor electrical conductivity, characterized in that, Includes the following steps: The two-dimensional material to be tested is deposited on a conductive substrate A to form a substrate with a single-layer thin film of two-dimensional material deposited on its surface; Subsequently, a conductive substrate B is placed parallel to the substrate under test, so that the conductive substrate B is in contact with the two-dimensional material monolayer film, and then encapsulated to form a sandwich structure of conductive substrate B, two-dimensional material monolayer film and conductive substrate A from top to bottom, thus obtaining the structure under test. Wherein, the conductive substrate A is a good conductive substrate; Under the condition of applied voltage, pressure is uniformly applied to the structure under test at a constant compression rate, and the change of current of the structure under test with the applied pressure is recorded to obtain pressure-current response data. The pressure-current response data were fitted using theoretical model formulas to obtain the pressure-current response curve of the two-dimensional material monolayer thin film, with a goodness of fit R. 2 >0.98000; obtained from the fitting results The ratio of the overlapping area between the two-dimensional material monolayer film and the conductive substrate B is used as the film coverage: The theoretical model formula is as follows: ; in, This represents the maximum contact area between two conductive substrates through a single layer of two-dimensional material. r It is a parameter that reflects sensitivity. P 0 is the pressure threshold. U For voltage, ρ For contact resistance resistivity, I The current is the response current of the structure under test.

2. The method as described in claim 1, characterized in that, The encapsulation process uses polyimide tape for encapsulation.

3. The method as described in claim 1, characterized in that, The two-dimensional material single-layer film is a discontinuous semiconductor or discontinuous insulating material with poor electrical conductivity.

4. The method as described in claim 1, characterized in that, The good conductive substrate is either Ni / Si or ITO / PET.

5. The method as described in claim 1, characterized in that, The conductive substrate B is a flexible substrate.

6. The method as described in claim 5, characterized in that, The flexible substrate is ITO / PET.

7. The method as described in claim 1, characterized in that, The applied voltage is 0.5~1.5V.

8. The method as described in claim 1, characterized in that, The compression rate is 5~25 mm / min.

Citation Information

Patent Citations

  • Nano pressure sensor and preparation method thereof

    CN111366275A